Efektifitas Terapi Akupuntur Terhadap Keberhasilan Rehabiltasi Pasien Pasca Stroke: Literature Review - Galih Noor Alivian; Koernia Nanda Pratama (Journal of Bionursing, 2022)
Introduction : Stroke is a sudden attack that occurs in the brain involving blood vessels in the brain (clogged or ruptured) and eventually manifests in various symptoms (starting from paralysis, difficulty speaking / slurred, swallowing disorders, and so on). This disease is divided into ischemic-infarction stroke and hemorrhagic stroke. In Indonesia, this disease has increased from 7% to 10.9%. This indicates that stroke is a disease that is quite dangerous and requires appropriate treatment or rehabilitation.Method: The search for journal articles was conducted electronically using several databases, namely DOAJ, PubMed and Google Scholar with the keyword "Acupunture for post stroke" for international journals, while for national journals using the Google Scholar search engine with the keywords "Acupuncture therapy for patients. post-stroke”, the journal sought is an intervention journal with the PICO frame work criteria (Patient, Intervention, Comparison, Outcome). From the results of the review, there were 5 journals that were relevant to the topic. The journal consists of 3 international journals and 2 national journals, the next step is to review the five journals.Result: Acupuncture therapy was effective to improve post-stroke rehabilitation. This therapy involves puncturing the Yang Ming Meridian to facilitate the flow of the Ci-Meridian. In these meridians there is an intricate system of connections called acupoints (acupuncture points) that bind or relate to various body functions and organs. In stroke patients, because some of the neural pathways have closed it is difficult to keep the circulation open. With acupuncture stimulation at some acupuncture points will open blood vessels and improve blood flow. based on the results obtained from these researchers that acupuncture is quite effective in the treatment of rehabilitation of stroke patients. In order to get maximum results, stroke patients are recommended not only to do acupuncture therapy. But also perform other therapeutic activities.Conclusion :Acupuncture therapy is effective on the success of post-stroke patient rehabilitation.